Quality Improvement: Fall Prevention In Cardiology Inpatients Aged 65 And Over - Amar Ahmed; Deep Ghaghda; Jordyn Tetro (Future Healthcare Journal)
Introduction: The elderly population of cardiology inpatients face a heightened risk of falls due to the compounded effects of cardiovascular disease on frailty, coupled with multiple antihypertensives patients are often placed on. This Quality Improvement Project (QIP) holds the primary objective of improving patient safety among cardiology inpatients aged >65, through a two-pronged approach: 1) ensure assessment of lying-standing blood pressure (LSBP) is complete and 2) optimisation of the bedside microenvironment. Materials and methods: Data was collected from cardiology inpatients aged 65 and above at Northwick Park Hospital, London using Cerner EPR and bedside assessment. Two snapshot data collection days, within a week, were conducted for each cycle. A reaudit was done 1 month after interventions were implemented. The following interventions were taken. Audit results were conveyed to the cardiology ward's charge nurse and falls champion, who opportunistically educated nursing staff on the significance and proper technique of LSBP measurements. Email reminders were dispatched, emphasising completion of patient bed boards with accurate mobility and transfer status, ensuring accessibility of mobility aids, and mandatory completion of LSBP measurements for all new admissions to the ward. Results: LSBP compliance initially at 12.8% significantly improved to 57.4% in Cycle 2 post-interventions. In terms of the bedside microenvironment, pre-intervention, 74.3% had a nearby call bell, 37.1% had noted mobility status, and 25.7% had a mobility aid, with 11.4% within reach. Post-intervention, these metrics improved, with 80.0% having a reachable call bell, 61.1% having noted mobility status, and from 35.6% of patients requiring a mobility aid, 75% were now within reach. Conclusion: Analysing both cycles demonstrated clear improvements in LSBP compliance and a strengthened commitment to a safe bedside environment. The challenge now lies in sustaining these positive changes. This necessitates the need for a cultural shift. Recommendations include a repeat audit in 6 months, sourcing mobility-specific bed boards, and introducing LSBP on the admission checklist electronic paperwork.